Kajian Energi Gelombang Laut Di Daerah Abrasi Serangai, Bengkulu Utara Melalui Pengamatan Tinggi Gelombang Laut - Ashar Muda Lubis; Yosi Apriani Putri; Rio Saputra; Juhendi Sinaga; M Hasanudin; Edi Kusmanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
The Serangai area, Batik Nau District, North Bengkulu has the highest average abrasion speed of 20 m/year. The abrasion could cause the coastal area to erode the coastline till several tens of meters. The purpose of this study was to determine the height of the ocean waves and to determine the energy of the ocean waves that has the potential to accelerate the abrasion process in the Serangai area. The research was carried out on November 5-7, 2018 in the Serangai beach area at a depth of 5 m using SBE 26 Plus Seagauge Wave equipment. The results showed that the observed wave height was between 0.8-1.6 m with a significant wave height (Hs) of 1.38 m. In addition, the wave period ranges from 5-11 s with a significant wave period (Ts) of 8.2 s. The result also shows that the maximum wave height of 1.6 m occurred on November 7, 2018 with maximum wave energy of 1800 J/m2. This result can perhaps accelerate the abrasion process in the Serangai area. It can also be seen that the wave height in the Serangai region is higher than in several other areas in Indonesia. However, it is necessary to continue observing the wave height to see the seasonal variations in sea wave height in Serangai area.